2022
DOI: 10.1111/are.16137
|View full text |Cite
|
Sign up to set email alerts
|

Identification, characterization and nutritional regulation of fatty acid‐binding protein ( fabp ) genes by vegetable oils in European seabass ( Dicentrarchus labrax ) reared in low water temperatures

Abstract: Vegetable oils (VOs) are preferred by the aquafeed industry as alternative oil sources to fish oil (FO) for sustainable aquaculture production because they decrease catching pressure for wild fish stocks, and compared with FO, VOs have higher annual production, easier accessibility and lower prices (Bayır et al., 2011). VOs are rich sources of 18C fatty acids (FAs), but their n-3 highly unsaturated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 114 publications
0
10
0
Order By: Relevance
“…Nonetheless, fabp10a / fabp10b and fabp11a / fabp11b responded in the same way to diet FAs (as indicated earlier), similar to their tissue‐specific transcription. The authors previously reported that spatio‐temporal changes in the various tissues and nutritional regulations of the D. labrax fabp10a / fabp10b and fabp11a / fabp11b genes were identical (Taşbozan et al ., 2022). Nonetheless, the results are complicated to evaluate due to the homeoviscous adaptation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, fabp10a / fabp10b and fabp11a / fabp11b responded in the same way to diet FAs (as indicated earlier), similar to their tissue‐specific transcription. The authors previously reported that spatio‐temporal changes in the various tissues and nutritional regulations of the D. labrax fabp10a / fabp10b and fabp11a / fabp11b genes were identical (Taşbozan et al ., 2022). Nonetheless, the results are complicated to evaluate due to the homeoviscous adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…temporal changes in the various tissues and nutritional regulations of the D. labrax fabp10a/fabp10b and fabp11a/fabp11b genes were identical (Tas ¸bozan et al, 2022). Nonetheless, the results are complicated to evaluate due to the homeoviscous adaptation.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations